Factors Affecting Electric Vehicle Buying Decision of Private Company Employees in Bangkok - siriyanon, supaluck; Choiejit, Ratchapan (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2024)
This study aims to: 1) investigate the factors influencing the purchase decision of electric vehicles (EVs) among private company employees in Bangkok, and 2) evaluate the cost-effectiveness of EV ownership for these consumers. Data was collected by calculating the Total Cost of Ownership (TCO) of internal combustion engine (ICE) vehicles, which includes the purchase price, fuel costs, maintenance expenses, leasing interest rates, depreciation rates, insurance premiums, and annual vehicle taxes. The relationship between independent and dependent variables was analyzed using Multiple Regression Analysis with the Ordinary Least Square Method (OLS), in conjunction with data gathered from questionnaires. The sample group comprised 200 employees of private companies in Bangkok and Metropolitan Region. Statistical measures employed in this research include mean and standard deviation. The study’s findings indicate that when comparing TCOs of EVs with similar purchase prices, the overall ownership costs are either comparable or show negligible differences. Moreover, the analysis of opinions on factors affecting the decision to purchase an EV reveals an average overall opinion score of 5.6969. Upon examining individual aspects, the highest average score pertains to government policies, followed by purchase intention, adherence to reference groups, and societal image influence, respectively.